DUKUNGAN SUAMI TERHADAP KESIAPAN IBU MEMBERIKAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS MUARA BATU KABUPATEN ACEH UTARA - Iryani Iryani; Cut Nurhasanah; Rosyita Rosyita; Irma Seriana; Yenni Fitri Wahyuni (PT. Intelek Cendikiawan Nusantara, 2026)
Background: Based on data from the Indonesian Health Profile in 2021, it shows that the coverage of babies who receive exclusive breastfeeding in Indonesia in 2021 is 56.9%. Meanwhile, in South Sulawesi Province, the coverage of babies who received exclusive breastfeeding in 2021 was 70.5%. It can be seen that this coverage has exceeded the program target in 2021, which is 40% (Ministry of Health of the Republic of Indonesia, 2021). The proportion of exclusive breast milk for 6 months (age 6 – 23 months) is 55.5%. The provinces with the highest proportion are the provinces of Jogjakarta (71.4%), NTB (68.7%), and Jambi (68.2%). The provinces with the lowest proportion are South Papua (33.4%), West Papua (35.9%) and Gorontalo (37.6%). Aceh is 26th (49.9) in terms of the Proportion of Exclusive Breastfeeding. Exclusive breastfeeding in North Aceh has only reached 45% of the target achieved at 75% and the Muara Batu Health Center has only reached 55%. Objective: To find out the relationship between husband support and the readiness of mothers to provide exclusive breastfeeding in the working area of the Muara Batu health center, North Aceh Regency. Methods: This study is a retrospective study or looks back at past circumstances and uses a quantitative approach. The design of this study is cross-sectional, identifying the relationship between variables with data measurement of independent variables and dependent variables only once at a time. The variables in this study were maternal characteristics (demographic data), husband support, and the success of exclusive breastfeeding research. Results: The relationship between husband support and exclusive breastfeeding as many as 36 respondents (69.2%) who gave exclusive breastfeeding received the husband's support, while 9 respondents (100%) who did not provide exclusive breastfeeding did not receive support in exclusive breastfeeding from their husbands. The results of the statistical test obtained a p-value of 0.000, which is <0.05, which means that it can be concluded that there is a relationship between husband support and exclusive breastfeeding. Conclusion: The influence of husband support on the readiness of mothers to provide exclusive breastfeeding in the working area of the Muara Batu Health Center, North Aceh Regency. Keywords : Exclusive Breastfeeding , Husband Support